Immunoadsorption apheresis versus intravenous immunoglobulin therapy for exacerbation of myasthenia gravis. (26th November 2021) - Yasuda, Manato; Uzawa, Akiyuki; Ozawa, Yukiko; Kojima, Yuta; Onishi, Yosuke; Akamine, Hiroyuki; Kuwabara, Satoshi
Abstract: Immunoadsorption apheresis (IA) or intravenous immunoglobulin (IVIg) is used to treat exacerbation of myasthenia gravis (MG). This study aimed to compare the efficacy and safety between IA and IVIg for MG patients with anti‐acetylcholine receptor (AChR) antibodies. We retrospectively studied 19 AChR antibody‐positive generalized MG patients who underwent IA (n = 9) or IVIg treatment (n = 10). We reviewed the MG activities of daily living profile (MG‐ADL) scores at baseline, 1 and 3 months after the treatment. Adverse events during the treatment period were also reviewed. The MG‐ADL scores showed significantly greater improvement from the baseline in the IA group than in the IVIg group (1 month: −7 vs −3, P  = .035; 3 months −9 vs −2.5, P  = .016). An adverse event that led to the discontinuation of the treatment was observed in only one patient in the IVIg group (anaphylactic reaction). Our data suggest that the IA treatment is safe and more efficacious than the IVIg treatment for aggravation of anti‐AChR‐positive MG. Larger prospective studies are required to confirm the finding.